Marketing Mix Strategy for Gold Installment Financing Products at Bank Syariah Indonesia Ponorogo - Himatul Kasanah; Nur Kasanah (MONETARIUM: Journal of Economics Business and Management, 2026)
This study aims to analyze the application of marketing mix strategies in gold installment financing products at Bank Syariah Indonesia (BSI) KCP Ponorogo, identify supporting and inhibiting factors for its implementation, and explain the impact of these strategies on increasing interest and the number of customers. This study was prepared from a field research-based thesis with a descriptive qualitative approach. Primary data were obtained through observations, interviews, and documentation of BSI KCP Ponorogo employees involved in the marketing and operation of gold installment products, while secondary data was obtained from internal documents, scientific literature, and relevant references. Data analysis was carried out using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the marketing strategy for gold installment products at BSI KCP Ponorogo is carried out through a combination of segmentation, targeting, and positioning (STP) approaches as well as the 7P marketing mix which includes product, price, place, promotion, people, process, and physical evidence. The product is positioned as a safe, liquid, and sharia-compliant long-term investment instrument through the murabahah contract. The marketing strategy highlights the ease of gold ownership through installment schemes, competitive prices, strategic office locations, the use of digital channels, direct promotion to agencies, the use of WhatsApp and physical promotional media, the quality of employee service, and a relatively easy transaction process. The main supporting factors include the ease of registration through digital channels, the character of gold as a relatively stable and liquid asset, service quality, and increasing public awareness of investment. Inhibiting factors include competition between financial institutions, uneven public literacy related to sharia gold installments, public perception that still associates gold with gold stores or pawnshops, and down payment policies that are considered burdensome for some potential customers. This study concludes that the 7P marketing mix has a positive effect on marketing effectiveness, strengthening product positioning, and increasing interest and number of gold installment customers. Thus, the marketing mix strategy has an important role in strengthening the competitiveness of gold installment financing products in Islamic banking at the branch level.